2011
DOI: 10.1016/j.biopsych.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interhemispheric Resting State Functional Connectivity in Cocaine Addiction

Abstract: Background Models of cocaine addiction emphasize the role of disrupted frontal circuitry supporting cognitive control processes. Yet, addiction-related alterations in functional interactions among brain regions, especially between the cerebral hemispheres, are rarely examined directly. Resting state fMRI approaches, which reveal patterns of coherent spontaneous fluctuations in the fMRI signal, offer a means to directly quantify functional interactions between the hemispheres. We examined interhemispheric resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
211
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(226 citation statements)
references
References 89 publications
13
211
1
Order By: Relevance
“…28 ' 29 Furthermore, a recent functional magnetic resonance study showed reduced prefrontal interhemispheric connectivity in cocaine-dependent participants relative to control subjects, in a network comprising bilateral lateral frontal, medial premotor, and posterior parietal areas. 30 The sort of connectivity measured by functional brain imaging only captures slow stationary correlations between blood flow amplitudes at different brain sites. Rapid and transient synchronization between distant brain regions can be measured using electrophysiological techniques.…”
Section: ~23mentioning
confidence: 99%
“…28 ' 29 Furthermore, a recent functional magnetic resonance study showed reduced prefrontal interhemispheric connectivity in cocaine-dependent participants relative to control subjects, in a network comprising bilateral lateral frontal, medial premotor, and posterior parietal areas. 30 The sort of connectivity measured by functional brain imaging only captures slow stationary correlations between blood flow amplitudes at different brain sites. Rapid and transient synchronization between distant brain regions can be measured using electrophysiological techniques.…”
Section: ~23mentioning
confidence: 99%
“…The corpus callosum, which is the largest area of white matter and is composed of association fibers in both hemispheres, plays an important role in interhemispheric communication and cognitive processes [14]. Altered white matter integrity in the corpus callosum may affect interhemispheric functional interactions [14][15][16], which are important for the integrity of brain functions [17]. However, OCD-related alterations in functional interactions between the cerebral hemispheres are rarely explored directly.…”
Section: Subjectsmentioning
confidence: 99%
“…A new measure, voxel-mirrored homotopic connectivity (VMHC), can quantify the homotopic patterns of RSFC by providing a voxelwise measure of connectivity between each voxel in one brain hemisphere and its mirrored voxel in the other [17]. Recently, the VMHC method has provided a variety of new disease-related findings on functional homology in cocaine addiction [15], schizophrenia [21], major depressive disorder [22,23], bipolar II disorder [24], autism [25] and drug-naive somatization disorder [26]. These findings demonstrate that VMHC can be regarded as a reliable and feasible measure to detect alterations in the functional homology between cerebral hemispheres in OCD patients.…”
Section: Subjectsmentioning
confidence: 99%
“…Previous results have shown enhanced connectivity within the anterior cingulate cortex network in cocaine-dependent individuals compared to controls (Camchong et al, 2011) as well as reduced prefrontal interhemispheric RSFC in cocaine users relative to control participants (Kelly et al, 2011). A handful of resting state cocaine studies have also examined functional connectivity between frontal and limbic brain areas (Cisler et al, 2013;Gu et al, 2010;Verdejo-Garcia et al, 2012;Wilcox et al, 2011) as cocaine addiction is characterized by persistent decision-making deficits, which are linked to functional abnormalities within the frontolimbic systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared to healthy controls, cocaine users show enhanced activation in the prefrontal brain regions during cue-induced cocaine craving (Grant et al, 1996;Wang et al, 1999;Wilcox et al, 2011). Resting-state fMRI approaches have revealed altered functional connectivity (RSFC) in frontal brain areas of cocaine users (Camchong et al, 2011;Kelly et al, 2011). RSFC, assessed by the correlation of spontaneous fluctuations of blood oxygen level-dependent (BOLD) signals in different regions of the resting brain, is believed to provide a measure of the brain's functional organization (Fox and Raichle, 2007).…”
Section: Introductionmentioning
confidence: 99%